Reduction of recombination effects in large plane parallel beam monitors for FLASH radiotherapy with scanned ion beams - Baack, Leon; Schuy, Christoph; Brons, Stephan; Horst, Felix; Voss, Bernd; Zink, Klemens; Haberer, Thomas; Durante, Marco; Weber, Uli (Physica medica, 2022)
Purpose: - Radiotherapy escalating dose rates above 50Gys−1, might offer a great potential in treating tumours while further sparing healthy tissue. However, these ultra-high intensities of FLASH-RT lead to new challenges with regard to dosimetry and beam monitoring. FLASH experiments at HIT (Heidelberg Ion Beam Therapy Center) and at GSI (GSI Helmholtz Centre for Heavy Ion Research) have shown a significant loss of signal in the beam monitoring system due to recombination effects. To enable accurate beam monitoring, this work investigates the recombination loss of different fill gases in the plane parallel ionisation chambers (ICs). - Methods: - Therefore, saturation curves at high intensities were measured for the currently used fill gases Ar/CO2 (80/20) and pure He and also for He/CO2 mixtures as alternative fill gases. Furthermore, breakdown voltages and ion mobilities were measured in ICs filled with He/CO2 mixtures. A numerical model for volume recombination in plane parallel ionisation chambers was developed and implemented in Python. This includes a novel simulation method of the space charge effect from the charge carriers in the detector volume and predicts a significant effect on the electric field for high intensity beams. - Results: - Even at high intensities the He/CO2 mixtures allow operation of the ICs at an electric field strength of 2 kVcm−1 or more which reduces recombination to negligible levels at intensities larger than 3 × 1010 12C-ions per second. Our measurements show that added fractions of CO2 to He decrease the ion mobility in the fill gas but significantly increase the breakdown voltage in the ICs compared to pure He.
Gesehen am 26.01.2022